2022
DOI: 10.1016/j.psj.2021.101553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary glucose oxidase on growth performance and intestinal health of AA broilers challenged by Clostridium perfringens

Abstract: Arbor Acre ( AA ) broilers were used as the research object to investigate whether glucose oxidase ( GOD ) has preventive and relieving effects on necrotic enteritis. The experiment was designed as a factorial arrangement of 2 dietary treatments × 2 infection states. Chickens were fed a basal diet or a diet with 150 U/kg GOD, and were challenged with Clostridium perfringens ( Cp ) or sterile culture medium. In our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This study also demonstrated that High dose C. perfringens inoculation impaired the development of the small intestinal morphology, weakened the villus morphology, decreased the ratio of villus height/crypt depth, and triggered an irreparable effect on the crypt depth in the small intestine. Some studies in broilers presented the same results in intestinal morphology ( 34 37 ). Other studies found that the C. perfringens enterotoxin (CPE), which is the main toxin produced by C. perfringens type A, displayed a dose-dependent effect and CPE can induce the intestinal injury ( 38 40 ).…”
Section: Discussionsupporting
confidence: 57%
“…This study also demonstrated that High dose C. perfringens inoculation impaired the development of the small intestinal morphology, weakened the villus morphology, decreased the ratio of villus height/crypt depth, and triggered an irreparable effect on the crypt depth in the small intestine. Some studies in broilers presented the same results in intestinal morphology ( 34 37 ). Other studies found that the C. perfringens enterotoxin (CPE), which is the main toxin produced by C. perfringens type A, displayed a dose-dependent effect and CPE can induce the intestinal injury ( 38 40 ).…”
Section: Discussionsupporting
confidence: 57%
“…There was no significant difference in the Alpha diversity index (Ace, Chao1, Simpson, and Shannon) of stool samples from the control group, the infection group, and the treatment group. Among the top 10 species with relative abundance at the phylum level (Figure e), Epsilonbacteraeota, as a pathological indicator of enteritis, had a significant increase in relative abundance after infection (Figure S6a,b), while the relative abundance of Firmicutes decreases after infection (Figure S6a,c). These indicate that mice may be induced to enteritis after Hp infection.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the ETEC challenge caused a minor shift in gastrointestinal pH value except for a reduction of colonic pH value, the related reason might deserve further research. Theoretically, gluconic acid produced by GOD catalysis can lower gastrointestinal pH value ( Zabek et al, 2020 ; Zhao et al, 2022 ). Unexpectedly, this study showed that GOD addition reduced pH value in the stomach instead of the intestine, probably because most of the intestinal gluconic acid produced by GOD catalysis was fermented into butyric acid by certain gut microbes such as Megasphaera elsdenii ( Tsukahara et al, 2002 ) that was detected to be increased in GOD group.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the increases in these beneficial bacteria coupled with the reductions in the above-mentioned harmful bacteria in the gut could at least partially clarify the observed conducive effects of GOD addition on growth and health parameters in challenged piglets. Similarly, limited studies in broilers revealed that GOD addition improved growth performance and intestinal health by optimizing gut microbial composition, as exhibited by the increases and decreases in certain beneficial and harmful bacteria, respectively ( Wu et al, 2019 ; Zhao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation